The reticulocyte restriction: invasion ligand RBP1a of Plasmodium vivax targets human TfR1, prohibitin-2, and basigin - Molina-Franky, Jessica; Röth, Daniel; Ararat‐Sarria, Monica; Patarroyo, Manuel Alfonso; Kalkum, Markus (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionPlasmodium vivax is the most widespread cause of malaria outside Africa. Developing effective controls is challenging because P. vivax exclusively invades reticulocytes, immature erythrocytes that are scarce and short-lived. This limits opportunities to culture the parasite and investigate the receptor-ligand interactions crucial for host cell invasion.MethodsThe erythroid cell lines JK-1 and BEL-A were evaluated in vitro as reticulocyte surrogates to assess their susceptibility to P. vivax invasion. Comparative membrane proteomics of these cell lines, reticulocytes, and mature erythrocytes were performed using quantitative liquid chromatography–mass spectrometry (LC-MS). Specific interactions between the parasite ligand PvRBP1a (residues 158–650) and candidate host receptors were identified by TurboID proximity labeling and validated through ELISA binding assays.ResultsWe confirmed that the JK-1 cell line supports P. vivax invasion and demonstrated for the first time that BEL-A cells are similarly susceptible, establishing both as effective surrogate models. Membrane proteomics identified several receptor candidates potentially involved in selective host-cell entry. In addition to known receptors, including transferrin receptor protein 1 (TfR1/CD71), CD98hc, and basigin (BSG), novel receptor candidates such as prohibitin-2 (PHB2), CAT-1 (SLC7A1), ATB(0) (SLC1A5), CD36, integrin beta-1 (ITGB1), and metal transporter CNNM3 were discovered. Proximity labeling with a recombinant PvRBP1a (158–650)-TurboID fusion protein confirmed the known interactions with TfR1 and BSG, and additionally identified PHB2 as a novel interacting partner. Notably, this is the first report implicating PHB2 as a co-receptor for P. vivax invasion.ConclusionOur findings provide novel insights into the molecular mechanisms underlying reticulocyte restriction in P. vivax. The JK-1 and BEL-A cell lines represent valuable platforms for dissecting receptor–ligand interactions during parasite invasion and for advancing the development of targeted therapeutic antimalarial strategies.